2023
DOI: 10.1055/s-0043-1774795
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does Microthrombosis Play in Long COVID?

Toshiaki Iba,
Jean M. Connors,
Jerrold H. Levy

Abstract: Soon after the outbreak of coronavirus disease 2019 (COVID-19), unexplained sustained fatigue, cognitive disturbance, and muscle ache/weakness were reported in patients who had recovered from acute COVID-19 infection. This abnormal condition has been recognized as “long COVID (postacute sequelae of COVID-19 [PASC])” with a prevalence estimated to be from 10 to 20% of convalescent patients. Although the pathophysiology of PASC has been studied, the exact mechanism remains obscure. Microclots in circulation can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…For the current compilation issue, we start with the contribution from Iba and colleagues. 1 As already noted, unexplained sustained fatigue, cognitive disturbance, and muscle ache/weakness are reported in patients who have recovered from an acute COVID-19 infection. This adverse condition, termed long-COVID or PASC, has a prevalence estimated to be around 10 to 20% of convalescent patients.…”
Section: Tablementioning
confidence: 82%
See 1 more Smart Citation
“…For the current compilation issue, we start with the contribution from Iba and colleagues. 1 As already noted, unexplained sustained fatigue, cognitive disturbance, and muscle ache/weakness are reported in patients who have recovered from an acute COVID-19 infection. This adverse condition, termed long-COVID or PASC, has a prevalence estimated to be around 10 to 20% of convalescent patients.…”
Section: Tablementioning
confidence: 82%
“…This issue begins with several manuscripts still focused on COVID-19 (coronavirus disease 2019) or its potential aftermath, a condition colloquially called “long-COVID,” and otherwise known as “post-acute sequelae of COVID-19 (PASC).” 1 2 3 Long-COVID represents a heterogeneous clinical syndrome characterized by a pathologic continuum of signs, symptoms, and also laboratory/radiologic abnormalities that may persist for a long time after recovering from an acute SARS-CoV-2 (severe acute respiratory syndrome-coronavirus disease 2) infection. Among the various components of this post-viral condition, the risk of venous thromboembolism (VTE) in patients hospitalized for COVID-19 remains considerably higher after discharge, especially in the earlier period (i.e., within the first 6–12 months), in older individuals, in men, in patients with longer hospital stays and more aggressive clinical management (e.g., mechanical ventilation and/or intensive care), when thromboprophylaxis is not used, and in those with a persistent pro-thrombotic state.…”
Section: Tablementioning
confidence: 99%
“…A recent study identified a disturbed retinal microcirculation to be strongly associated with PCS and ME/CFS, which may serve as a potential marker for microcirculatory disorders [10,42]. Notably, the thrombo-inflammatory status persists months after the patient has recovered and the virus has cleared [5,40,43]. Therefore, malformed blood cells, microclots, and thrombo-inflammation can potentially impede capillary perfusion and promote a microcirculatory disorder and thus impair organ blood supply via capillary obstruction [9].…”
Section: Microcirculatory Disturbances In Me/cfs and Pcsmentioning
confidence: 99%
“…Predominant roles of platelets contributing to the development of vaccine-induced immune thrombotic thrombocytopenia (VITT) are also recognized in conjunction with the polyanion from the vaccine component 3) (Figure 1). Moreover, there is speculation about the potential involvement of activated platelets in the pathogenesis of the condition known as 'Long COVID' 4) .…”
mentioning
confidence: 99%